Focal adhesion kinase plays an essential role in Th17 cell differentiation by stimulating NF-κB signaling - Kim, Hyeong Su; Lee, Ji Hyeon; Sohn, Hyogon; Lee, Woo Ho; Kim, Ga Eul; Lee, Wonyong; Kim, Hang-Rae; Lee, Gap Ryol (Frontiers in Immunology, 2025)
T helper type 17 (Th17) cells play critical roles in the pathogenesis of various autoimmune and inflammatory diseases; however, signaling pathways that affect Th17 cell differentiation are not fully understood. Here, we investigated whether focal adhesion kinase (FAK), an integrator of extracellular signals, regulates differentiation of Th17 cells. The findings reveal that Fak deficiency in CD4 T cells significantly reduces Th17 differentiation, while also promoting regulatory T (Treg) cell differentiation, thereby ameliorating symptoms of experimental autoimmune encephalomyelitis (EAE). Mechanistically, Fak deficiency inhibited nuclear translocation of the NF-κB subunit RelA, thereby reducing the binding of RelA to the promoter region of Il17a. Moreover, pharmacological inhibition of FAK with the specific inhibitor PND1186 prevented Th17 differentiation in vitro, and reduced EAE symptoms in vivo. Thus, FAK plays an essential role in Th17 cell differentiation by stimulating NF-κB signaling.